Analisis Yuridis Dampak Pasca Pandemi Covid-19 Terhadap Lelang Eksekusi Hak Tanggungan Dari Perbankan Pada KPKNL Medan - Ade Liniarty Daulay; M. Citra Ramadhan; Isnaini Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this writing is to analyze the auction mechanism for executing mortgages from banks, the role of the KPKNL in carrying out the execution of mortgages and the obstacles faced by the KPKNL in carrying out the auction. The research method used is normative juridical. The research data comes from secondary data which comes from primary legal materials, secondary legal materials and tertiary legal materials which are then analyzed qualitatively. The results of the first study, that the execution auction of mortgage rights is carried out by creditors by submitting an application for execution of mortgage rights to the head of the local District Court where the collateral object is located. If the Debtor does not fulfill his obligations for a maximum of 8 (eight) days both for repayment and discharge or if he is summoned properly, cannot appear, then the chairman of the court by his position gives an order by letter, to confiscate the object of collateral right to be sold through auction general for payment. Second, the role of the KPKNL, as a government agency in executing the Mortgage Auction, as a supervisor so that auction items are not misused, as a selection agency for Mortgage auction participants, as a guard for the stability of Mortgage auction implementation, as an intermediary between buyers and sellers of auctioned goods. Third, in the implementation of the auction, some of the obstacles faced by the State Property and Auction Service Office are internal constraints and external constraints.